What are the priorities for investment in improved nutrition data? - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
Twice annually, Uganda implements Child Days Plus (CDP), a month-long outreach activity that distributes vitamin A capsules to preschool children and deworms children 6 months to 14 years old. Introduced initially as a temporary, interim strategy, CDP is now a decade old.To assess how well CDP is implemented using an activity-based cost analysis.In the absence of a cost-accounting system for CDP, we defined the six major CDP activities as cost centers and identified five important subactivities required to implement a round of CDP. Based on a purposive sample, we conducted a structured interview survey of 59 Ministry of Health facilities, 9 district offices, and national-level CDP staff.Only one-third of the facilities implemented all 11 CDP core activities. The survey revealed that Ministry of Health staff and volunteers are frequently paid substantially less in allowances than they are entitled to for their CDP outreach activities. Viewing these two practices—nonimplementation and less-than-full-reimbursement—as indicators of CDP's underfinancing, we estimate the program is underfinanced by the equivalent of 37% of its “full implementation” costs. Two-thirds of underfinancing is manifested in nonimplementation and one-third as less-than full-reimbursement. CDP exploits economies of scale and scope and has an average cost per child served of US$0.22. We estimate that it annually saves 367,000 disability-adjusted life-years (DALYs) at an average cost of US$12.5, making it—despite its underfinancing—highly cost-effective.Increased CDP funding would enable its vitamin A coverage rate of 58% and its deworming coverage rate of 62% to be increased, thereby increasing its effectiveness and efficiency. CDP should be “relaunched,” as part of an effort to improve the structure of the program, set expectations about it, and earmark a minimum of resources for CDP. The Ministry of Health should demonstrate its new, greater commitment to CDP by introducing a program-specific budget line item, increasing CDP's budget allocation, and developing and implementing a training program that identifies the minimum uniform activities required to implement CDP.